2001
DOI: 10.1046/j.1365-2273.2001.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, single-blind, randomized controlled trial of antiseptic cream for recurrent epistaxis in childhood

Abstract: Epistaxis is common in children. Trials show antiseptic cream is as effective as cautery, but it is not known whether either is better than no treatment. We wished to know the efficacy of cream in children with recurrent epistaxis. The design was a single-blind, prospective, randomized controlled trial set in the Otolaryngology clinic in a children's hospital. The participants were 103 children referred by their general practitioner for recurrent epistaxis. Excluded were those with suspected tumours, bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 6 publications
2
61
1
2
Order By: Relevance
“…1,12 Topical antiseptic cream does appear to assist in reducing the frequency of nosebleeds in clinical practice, and a randomised control trial of 103 children demonstrated that 4 weeks treatment with 0.5% neomycin+0.1% chlorhexidine cream (naseptin) is effective (relative risk reduction 47%, absolute risk reduction 26%, number needed to treat 3.8), although not statistically significant, according to recent a Cochrane review. 18 In present study 61% of traumatic patients managed with observation alone whereas 55.8% of inflammatory group and 66.7% of blood dyscrasia group needed nasal packing for control of epistaxis. In children with epistaxis secondary to underlying haematological coagulopathies, the primary focus is on correcting underlying clotting problems where possible, and/or the use of topical haemostatic agents.…”
Section: Discussionmentioning
confidence: 48%
“…1,12 Topical antiseptic cream does appear to assist in reducing the frequency of nosebleeds in clinical practice, and a randomised control trial of 103 children demonstrated that 4 weeks treatment with 0.5% neomycin+0.1% chlorhexidine cream (naseptin) is effective (relative risk reduction 47%, absolute risk reduction 26%, number needed to treat 3.8), although not statistically significant, according to recent a Cochrane review. 18 In present study 61% of traumatic patients managed with observation alone whereas 55.8% of inflammatory group and 66.7% of blood dyscrasia group needed nasal packing for control of epistaxis. In children with epistaxis secondary to underlying haematological coagulopathies, the primary focus is on correcting underlying clotting problems where possible, and/or the use of topical haemostatic agents.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies have reported on children with recurrent minor epistaxes [4][5][6] but our study appears to be the first to examine the outcomes of children with acute severe epistaxis requiring hospital admission. The data suggests that epistaxis requiring hospital admission is uncommon in healthy children, with only 14 admissions over a 10-year-period to a major pediatric center, and that the incidence of underlying serious pathology is low.…”
Section: Discussionmentioning
confidence: 97%
“…6 Moreover, epistaxis can be treated by compression and oxymetazoline alone in 65% of cases, implying that many ED visits for epistaxis could be preventable. 7 Knowledge of the frequency of ED epistaxis visits, mode of arrival, and disposition is a prerequisite to determining the utility of preventive efforts.…”
Section: Importancementioning
confidence: 99%